PENGARUH KEPUASAN KONSUMEN TERHADAP PENJUALAN PT. TUNAS DWIPA MATRA - Tri Wulandari; Retno Sri Handini (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
In carrying out its business as a Honda motorbike distributor, PT. Tunas Dwipa Matra faces a problem, namely increasingly fierce competition between market shares, each market share competes to provide the best service to provide satisfaction to consumers. Based on this, the problem is: How much customer satisfaction can influence sales at PT. Tunas Dwipa Matra and How Satisfaction Influences Sales at PT. Tunas Dwipa Matra. The purpose of this research is to find out how satisfaction affects sales at PT. Tunas Dwipa Matra The hypothesis proposed is that: Sales have a positive influence on customer satisfaction at PT. Tunas Dwipa Matra. The research method includes: the variable studied is service (independent variable) which consists of three elements, namely presale service, product service and sales service and consumer satisfaction (dependent variable). The population is consumers who buy Honda motorbikes in 2023, namely 5450 people. Based on the calculations, a sample of 99 people was used, the sampling was carried out using Random Sampling Technique. This research uses qualitative and quantitative analysis methods using minimum index values, maximum index values ​​and intervals. Based on the research results, the respondents' answers were obtained with a final score of 6723 which was in the high measurement level class with a value between 5941-7920. Means the level of consumer satisfaction with sales services at PT. Tunas Dwipa Matra is classified at a high level. This shows that large sales have a positive and significant influence on consumer satisfaction. Thus it can be concluded that the hypothesis proposed is acceptable. In addition, of the three sales indicators, the pre-sales service indicator provides the highest contribution, followed by product service and sales. Keywords: Sales Service, Customer Satisfaction.